M|G|∞ Queue Parameters Values Approximation Through a Markov Renewal Process - Ferreira, M. A. M. (arXiv:2210.02508, 2025)
Some M|G|∞ queue systems parameters values approximations, obtained through the consideration of an adequate Markov renewal process, are presented, and studied.